Clinical benefit without sweat chloride response after ETI therapy in an adult with cystic fibrosis bearing the L467F;F508del complex CFTR allele: a case report and the role of AI-assisted chest CT in longitudinal monitoring - Marcela Kreslova; Daan Caudri; Isabelle Sermet-Gaudelus; Aurelie Hatton; Punitkumar Makani; Vaclav Koucky; Malgorzata Libik; Hana Hrdinova; Libor Fila; Nela Stastna; Eva Furstova; Radka Bittenglova; et al. (Frontiers in Medicine, 2026)
Background Elexacaftor/tezacaftor/ivacaftor (ETI) is the standard of care for most people with cystic fibrosis (CF) who carry at least one F508del allele. However, predicting responses to CFTR modulators in rare or complex CFTR genotypes is challenging. Sweat chloride concentration (SCC) and patient-derived functional assays assessing CFTR-mediated chloride transport are commonly used to classify modulator responsiveness. Carriers of the p.Leu467Phe;p.Phe508del (henceforward legacy nomenclature: L467F;F508del) complex CFTR allele have been considered unlikely to respond to ETI, based on short-term clinical, biomarker and ex vivo evidence. We report a discordant long-term response in an adult carrying this complex allele, with clinically meaningful benefit despite persistently negative CFTR chloride transport biomarkers. Case presentation We describe an 8-year longitudinal pre- and post-treatment assessment of an adult woman with CF, adherent to therapy, with the L467F;F508del complex allele compounded with the non-responsive c.489 + 1G > T (621 + 1G > T) variant in trans . She has pancreatic insufficiency, progressive lung disease, and recurrent pulmonary exacerbations. After ETI commencement (at 40.5 years; July 2021) SCC remained unchanged at ∼100 mmol/L. Intestinal organoid and primary nasal epithelial cell assays showed no measurable ETI-related CFTR-mediated chloride transport rescue. Nevertheless, BMI increased from 22.0 to 26.8 kg/m 2 , annual exacerbations decreased from 5 to 3, and ppFEV₁ improved from 51% to 55–59%. Serial chest CT showed a shift from pre-ETI progression to post-ETI stabilisation, with reductions in air trapping and the extent of bronchiectasis on manual Brody II scoring and LungQ/PRAGMA-AI quantification. Exploratory in vitro exposure of nasal epithelial cells to vanzacaftor/tezacaftor/ivacaftor yielded ∼5% CFTR-mediated rescue, contrasting with the negative ETI response. Conclusion Persistent CFTR biomarker negativity may not fully exclude clinically meaningful ETI-associated benefit in rare or complex CFTR genotypes. The pulmonary and extrapulmonary improvements observed in this case support multidimensional response assessment beyond single-biomarker endpoints. These hypothesis-generating observations support individualised long-term monitoring and comprehensive interpretation of CFTR biomarkers in the clinical context. AI-assisted chest CT may provide complementary real-world evidence. An exploratory in vitro rescue study with vanzacaftor/tezacaftor supports the evaluation of emerging CFTR modulators. It suggests that similar studies should be conducted in other cases involving complex CFTR alleles.